2017
DOI: 10.1152/ajplung.00134.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term maternal smoking on the offspring’s lung health

Abstract: Maternal smoking during pregnancy contributes to long-term health problems in offspring, especially respiratory disorders that can manifest in either childhood or adulthood. Receptors for advanced glycation end products (RAGE) are multiligand receptors abundantly localized in the lung, capable of responding to by-products of reactive oxygen species and proinflammatory responses. RAGE signaling is a key regulator of inflammation in cigarette smoking-related pulmonary diseases. However, the impact of maternal ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 63 publications
(68 reference statements)
2
26
0
Order By: Relevance
“…Smoking can affect the functions of multiple organ system, including the lung, brain, heart, and kidney. It is clear from this and our previous studies, such impact can be transferred to the next generation, including that of nicotine addiction and substance abuse ( Yohn et al, 2015 ; Chan et al, 2016b ; Vivekanandarajah et al, 2016 ; Yuan et al, 2016 ; Sukjamnong et al, 2017 ). The programming in offspring can also be long-lasting as shown in other studies, especially the impact on neurocognitive changes such as increased anxiety-like behavior in this study ( Mueller and Bale, 2007 , 2008 ; Vassoler and Sadri-Vakili, 2014 ; Bale, 2015 ).…”
Section: Discussionmentioning
confidence: 57%
“…Smoking can affect the functions of multiple organ system, including the lung, brain, heart, and kidney. It is clear from this and our previous studies, such impact can be transferred to the next generation, including that of nicotine addiction and substance abuse ( Yohn et al, 2015 ; Chan et al, 2016b ; Vivekanandarajah et al, 2016 ; Yuan et al, 2016 ; Sukjamnong et al, 2017 ). The programming in offspring can also be long-lasting as shown in other studies, especially the impact on neurocognitive changes such as increased anxiety-like behavior in this study ( Mueller and Bale, 2007 , 2008 ; Vassoler and Sadri-Vakili, 2014 ; Bale, 2015 ).…”
Section: Discussionmentioning
confidence: 57%
“…Our previous studies in mice have repeatedly shown that MSE can reduce the level of endogenous antioxidant Manganese Superoxide Dismutase in the brain, kidney, and lungs of adult offspring accompanied by increased Reactive Oxygen Species (ROS) levels in those organs; interestingly, antioxidant supplementation during pregnancy could completely or partially reverse the adverse effects on those organs induced by MSE (Chan et al, 2017;Sukjamnong et al, 2017Sukjamnong et al, , 2018. The endogenous antioxidant enzyme system is established in the second and third trimester of pregnancy and continues to develop in early childhood (Fanucchi, 2004).…”
Section: The Role Of Oxidative Stress In the Development Of Asthma Inmentioning
confidence: 99%
“…In this instance, perhaps only epigenetic modification can explain such prolonged impairment in brain antioxidant capacity long after the maternal source of oxidants are removed . This may also explain why short‐term antioxidant supplement in the mothers during pregnancy and lactation can have such long‐lasting effect to boost endogenous antioxidant capacity in the offspring . Breastfeeding has been shown to protect the child from various metabolic conditions partially due to antioxidants in the breastmilk.…”
Section: Potential Cellular Mechanismsmentioning
confidence: 99%
“…75 This may also explain why short-term antioxidant supplement in the mothers during pregnancy and lactation can have such long-lasting effect to boost endogenous antioxidant capacity in the offspring. 4,[76][77][78] Breastfeeding has been shown to protect the child from various metabolic conditions partially due to antioxidants in the breastmilk. However, its protection of smokers' offspring seems to be limited.…”
Section: Oxidative Stress In the Brainmentioning
confidence: 99%